Teacher competence in the use of music learning media in primary schools - Resa Respati; Anggit Merliana; Riefki Fiestawa; Rosarina Giyartini; Nindi Citra Setia Dewi (EduStream: Jurnal Pendidikan Dasar, 2026)
Teacher competence is an important factor in optimizing the use of instructional media to create meaningful musical experiences for students, particularly among classroom teachers who do not have a formal educational background in music but are still responsible for teaching music. This study aims to analyze the influence of elementary school teachers’ competence on the use of music learning media. This research employs an explanatory quantitative approach involving a sample of 271 elementary school teachers from five regions in West Java Province, namely Tasikmalaya, Ciamis, Banjar, Garut, and Pangandaran, selected through stratified random sampling. Data were collected using a Likert-scale questionnaire (reliability α = 0.648 for teacher competence and α = 0.874 for media use) and analyzed using simple linear regression. The results indicate a positive and significant effect of teacher competence on the use of music learning media, with a significance value of 0.000 (< 0.05) and a coefficient of determination (R²) of 0.443. This finding shows that teacher competence explains 44.3% of the variation in the use of learning media. The higher the level of teacher competence, the more effective the use of instructional media becomes. Therefore, strengthening teachers’ professional and pedagogical competence is a key factor in improving the quality and effectiveness of music learning in elementary schools